Surveillance of genetic drift in Influenza A virus with base-specific cleavage and MALDI-TOF mass spectrometry - Gao, Xiang (2013)
With the discovery of several matrices which enable the ionization of DNA and RNA, MALDI mass spectrometry has become a powerful platform for the study of nucleic acid sequence changes, (e.g. mutations, single nucleotide polymorphisms (SNPs), insertion/deletion, alternative splicing, etc.), amount changes (e.g. copy number variation, gene expression, allele expression, etc.), as well as modifications (e.g. methylation of genomic DNA, post transcriptional modification of tRNAs and rRNAs). Two major strategies have been employed to characterize these changes. Primer extension reactions are designed for genotyping of known polymorphic sites and determining the levels of gene or allele expressions. Base-specific cleavage reactions are used for discovery of unknown polymorphisms and characterization of modifications. These two assays usually generate nucleic acid fragments less than 30 bases long, which is the ideal mass range for MALDI mass spectrometry. Treatments of influenza infection are most effective if administered within 36 to 48 hours after the onset of symptoms. To develop a rapid and inexpensive diagnostic method, base-specific cleavage followed by MALDI-TOF mass spectrometry analysis has been used for high throughput and high resolution identification of all species of influenza viruses. A signature region of 300 to 800 base pairs in length from the viral genome is transcribed and then digested with RNase A to produce a strain-specific set of mass peaks, which serve as a molecular weight fingerprint. This approach has great potential in the surveillance of global spread and emergence of novel viral genotypes especially from antigenic drift.In this project, the approach is evaluated using Influenza A/WSN/1933 and A/PR/8/1934 viral strains. The molecular weight fingerprints obtained from mass spectrometric data cover more than 90% of the genomic sequence in query, and in perfect agreement with DNA sequencing result, suggesting that the rapid identification method is feasible and accurate. Treatments of influenza infection are most effective if administered within 36 to 48 hours after the onset of symptoms. To develop a rapid and inexpensive diagnostic method, base-specific cleavage followed by MALDI-TOF mass spectrometry analysis has been used for high throughput and high resolution identification of all species of influenza viruses. A signature region of 300 to 800 base pairs in length from the viral genome is transcribed and then digested with RNase A to produce a strain-specific set of mass peaks, which serve as a molecular weight fingerprint. This approach has great potential in the surveillance of global spread and emergence of novel viral genotypes especially from antigenic drift. In this project, the approach is evaluated using Influenza A/WSN/1933 and A/PR/8/1934 viral strains. The molecular weight fingerprints obtained from mass spectrometric data cover more than 90% of the genomic sequence in query, and in perfect agreement with DNA sequencing result, suggesting that the rapid identification method is feasible and accurate.